The Foreign Corrupt Practices Act: The Failure of the Self-Regulatory Model of Corporate Governance in the Global Business Environment - Weismann, Miriam F. (Journal of business ethics, 2009)
The American regulatory model of corporate governance rests on the theory of self-regulation as␣the most effective and efficient means to achieve corporate self-restraint in the marketplace. However, that model fails to achieve regular compliance with baseline ethical and legal behaviors as evidenced by a century of repeated corporate debacles, the most recent being Enron, WorldCom, and Refco. Seemingly impervious to its domestic failure, Congress imprinted the same self-regulation paradigm on legislation restraining global business behavior, the Foreign Corrupt Practices Act. This anti-bribery initiative prohibits unethical and illegal payments made to foreign public officials in an effort to eradicate bribery as a rational-choice global market entry strategy. However, this paper illustrates, using newly complied statistics from 1977 to 2008, that the FCPA has not had a dramatic impact on U.S. global corporate behavior despite its recent high profile coverage and the tough regulatory rhetoric about corporate compliance. The paper also extends the prior Cragg and Woof FCPA efficiency study and provides current empirical evidence to resolve several unanswered questions raised by that earlier study.